2018
DOI: 10.1021/acsami.8b01906
|View full text |Cite
|
Sign up to set email alerts
|

Initial Cell Adhesion onto a Phospholipid Polymer Brush Surface Modified with a Terminal Cell Adhesion Peptide

Abstract: Dynamic changes in the properties of adsorbed protein layers at material surfaces make it difficult to analyze a cell adhesion behavior. Adhesion is affected by the ligand molecules in the adsorbed protein layers on the material's surface. This study aimed to quantitatively analyze the initial cell adhesion onto a polymeric surface modified with immobilized cell adhesion molecules with a well-defined structure. Peptides containing an arginine-glycine-aspartic acid (RGD) sequence were introduced at almost all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…The procedure to immobilize the functional peptides at the terminal of the surface PMPC chains is briefly described as follows. , A methanol solution of NaN 3 was added to the polymerization solution to adjust the final concentration to 50 mmol/L, and then stirred at 40 °C overnight. After the substrates were removed from the solution and rinsed with methanol (PMPC-N 3 graft substrate), the substrates were immersed in a mixture of dimethyl sulfoxide (DMSO) and water (80/20 by volume) containing 0.30 mmol/L of each oligopeptide, 1.0 mmol/L Cu­(II)­SO 4 5H 2 O, and 10 mmol/L l -ascorbic acid sodium salt.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure to immobilize the functional peptides at the terminal of the surface PMPC chains is briefly described as follows. , A methanol solution of NaN 3 was added to the polymerization solution to adjust the final concentration to 50 mmol/L, and then stirred at 40 °C overnight. After the substrates were removed from the solution and rinsed with methanol (PMPC-N 3 graft substrate), the substrates were immersed in a mixture of dimethyl sulfoxide (DMSO) and water (80/20 by volume) containing 0.30 mmol/L of each oligopeptide, 1.0 mmol/L Cu­(II)­SO 4 5H 2 O, and 10 mmol/L l -ascorbic acid sodium salt.…”
Section: Methodsmentioning
confidence: 99%
“…Surface-initiated atom transfer polymerization (SI-ATRP) was carried out using a glass substrate coated with gold. 59 Gold thin films were formed on glass substrates using the high-frequency magnetron sputtering system (VTR-150M/SRF (SCOTT-C3), ULVAC, Inc., Kanagawa, Japan). First, chromium was sputtered at a thickness of 10 nm on the glass substrate (1.2 × 2.4 × 0.2 cm 3 ), and then gold was sputtered at a thickness of 200 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoarchitectonics essence can be introduced to intercell spaces within cell assemblies to produce artificial cell-cell communication for the cell-to-cell functional relations. In addition, material developments for nanoarchitected platforms for cell adhesion such as self-assembled phosphate-polyamine networks [ 155 ] and biocompatible polymer brushes [ [156] , [157] , [158] ] have been continuously researched. These efforts would bring us much closer to the final goals of nanoarchitectonics, the creation of living creature–like functional systems.…”
Section: Perspectivementioning
confidence: 99%
“…In this regard, massive research reported that high affinity to cells could be achieved by endowing a substrate with adhesive molecules such as fibronectin [ 22 ] and Arg‐Gly‐Asp (RGD). [ 23,24 ] Unfortunately, such biomolecules lack cell specificity due to the widespread receptors on multiple cell types, and even run the risk of inducing differentiation of MSCs. [ 25,26 ] To overcome these limitations, a peptide sequence EPLQLKM (E7) [ 27 ] with high and specific affinity to the rat bone marrow‐derived mesenchymal stem cells (rBMSCs) has been discovered and used.…”
Section: Introductionmentioning
confidence: 99%